Efektivitas Konseling Online Berbasis Solution Focused Brief Counseling untuk Mengurangi Stres Akademik pada Siswa SMP - Oktavianas, Andri; Nurihsan, Juntika; Saripah, Ipah (Indonesian Journal of Counseling and Development, 2025)
Academic stress is a prevalent psychological concern among junior high school students, particularly due to the increasing academic demands and the widespread adoption of online learning. This form of stress can impair students' academic performance and compromise their psychological well-being. Consequently, there is a growing need for counseling interventions that are both effective and adaptable to the digital learning environment. The present study examines the effectiveness of online Solution Focused Brief Counseling (SFBC) in alleviating academic stress in junior high school students. Utilizing a quasi-experimental design with a pretest-posttest control group structure, the study involved 10 students assigned to either an experimental or a control group. The experimental group participated in four online counseling sessions, while the control group received no intervention. Data were analyzed using descriptive statistics. Given the small sample size, non-parametric analysis was conducted using the Wilcoxon Signed Rank Test to compare pretest and posttest scores in the experimental group. Results demonstrated a significant reduction in academic stress scores within the experimental group, decreasing from an average of 120.8 to 101.6, whereas the control group exhibited an increase from 128.6 to 131.8. The Wilcoxon Signed Rank Test yielded a statistically significant result (p = 0.042, p < 0.05), confirming the efficacy of the intervention. These findings suggest that online SFBC represents a viable and effective counseling strategy for mitigating academic stress among junior high school students, offering a flexible psychological intervention well-suited to the demands of distance learning and digital education contexts